Final-stage diversion: a safety net for offenders with mental disorders - Fiduccia, Chelsea E. (Criminal justice and behavior, 2012)
Diversion programs for offenders with mental disorders typically focus on early intervention as the ideal avenue for redirecting individuals from the criminal justice system. Although this approach is advantageous in many respects, sentenced offenders on probation have few available options for the intensive treatment provided by such programs. ATLAS, a mental health court in Dallas, Texas, adopts a reverse approach in selecting individuals on the brink of probation revocation. When compared to a matched sample, ATLAS participants had lower rates of rearrest within 12 and 24 months of their intake, supporting the efficacy of final-stage diversion programs as a pragmatic alternative to early interventions.